2020
DOI: 10.1055/s-0040-1708483
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-Aspartate Receptor Hypofunction in Meg-01 Cells Reveals a Role for Intracellular Calcium Homeostasis in Balancing Megakaryocytic-Erythroid Differentiation

Abstract: The release of calcium ions (Ca2+) from the endoplasmic reticulum (ER) and related store-operated calcium entry (SOCE) regulate maturation of normal megakaryocytes. The N-methyl-D-aspartate (NMDA) receptor (NMDAR) provides an additional mechanism for Ca2+ influx in megakaryocytic cells, but its role remains unclear. We created a model of NMDAR hypofunction in Meg-01 cells using CRISPR-Cas9 mediated knockout of the GRIN1 gene, which encodes an obligate, GluN1 subunit of the NMDAR. We found that compared with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In fact, altered neuregulin 1-ErbB4 signaling is a wellestablished mechanism of NMDAR hypofunction in schizophrenia (Hahn et al, 2006). Encouragingly, we also found that in Meg-01-GRIN1 −/− cells, transcripts for neuregulin 1 and ErbB receptor feedback inhibitor 1 were up-regulated (1.98-and 2.05-fold, respectively), implying the ErbB4-NMDAR link is maintained during megakaryocytic-erythroid differentiation (Hearn et al, 2020).…”
Section: Nmdar Effects On Megakaryocytic Differentiationsupporting
confidence: 58%
See 4 more Smart Citations
“…In fact, altered neuregulin 1-ErbB4 signaling is a wellestablished mechanism of NMDAR hypofunction in schizophrenia (Hahn et al, 2006). Encouragingly, we also found that in Meg-01-GRIN1 −/− cells, transcripts for neuregulin 1 and ErbB receptor feedback inhibitor 1 were up-regulated (1.98-and 2.05-fold, respectively), implying the ErbB4-NMDAR link is maintained during megakaryocytic-erythroid differentiation (Hearn et al, 2020).…”
Section: Nmdar Effects On Megakaryocytic Differentiationsupporting
confidence: 58%
“…In keeping with the pro-erythroid pattern of transcription factors, Meg-01-GRIN1 −/− cells displayed features of erythroid differentiation (Figure 1Biii). Our data provide the first evidence that NMDARs comprise an integral component of the Ca 2+ toolkit in megakaryocytic cells, and argue that intracellular Ca 2+ homeostasis may be more important than currently recognized for balancing megakaryocytic with erythroid differentiation at the level of a common progenitor (Hearn et al, 2020).…”
Section: Nmdar Effects On Megakaryocytic Differentiationmentioning
confidence: 68%
See 3 more Smart Citations